Vaccine and Immunotherapeutic Approaches for the Prevention of Cryptococcosis: Lessons Learned from Animal Models - Wormley, Floyd L.; Hole, Camaron R. (Frontiers in Microbiology, 2012)
Cryptococcus neoformans and Cryptococcus gattii, the predominant etiological agents of cryptococcosis, can cause life-threatening infections of the central nervous system in immunocompromised and immunocompetent individuals. Cryptococcal meningoencephalitis is the most common disseminated fungal infection in AIDS patients, and C. neoformans remains the third most common invasive fungal infection among organ transplant recipients. Current anti-fungal drug therapies are oftentimes rendered ineffective due to drug toxicity, the emergence of drug resistant organisms, and/or the inability of the host’s immune defenses to assist in eradication of the yeast. Therefore, there remains an urgent need for the development of immune-based therapies and/or vaccines to combat cryptococcosis. Studies in animal models have demonstrated the efficacy of various vaccination strategies and immune therapies to induce protection against cryptococcosis. This review will summarize the lessons learned from animal models supporting the feasibility of developing immunotherapeutics and vaccines to prevent cryptococcosis.